Tantangan Guru Reguler Dalam Implementasi Pendidikan Inklusif: Studi Kasus di Sekolah Dasar - Ghasani, Azmi; Sulaiman , Zoni; Gunawan, Dani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education is the main pillar in providing equal access to education, but in practice, regular teachers are often the ones most affected by various implementation obstacles. This research aims to describe in depth the challenges faced by regular teachers in implementing inclusive education at SDN Regol 6. Using a descriptive qualitative approach, data was collected through in-depth interview techniques with first grade teachers and analyzed using data reduction methods, data presentation, and drawing conclusions to obtain a holistic picture. The research results show that regular teachers at SDN Regol 6 face serious challenges that are multidimensional. First, the absence of Special Guidance Teachers (GPK) forces regular teachers to carry a double burden, where they have to carry out the role of main educators as well as special assistants for Students with Special Needs (PDBK). This condition causes an imbalance in learning focus, where regular students are often neglected in order to handle the intensive needs of GDPK. Second, the low level of special pedagogical competence due to the lack of formal training forces teachers to carry out independent digital literacy which is not necessarily comprehensive. Third, limited physical facilities, such as the absence of disabled toilets, ramp access, and special learning media, become physical obstacles for teachers in creating independent learning for students. Fourth, teachers face significant psychological and emotional pressure due to communication barriers with students' parents who tend not to accept their children's special needs. This rejection from the family hampers educational synergy and increases the mental burden on class teachers. This research concludes that the challenges faced by regular teachers are not just administrative technical, but touch managerial and emotional aspects that require systemic support in the form of providing experts, improving infrastructure, and continuing education for students' parents.